2020
DOI: 10.15294/kemas.v16i1.12636
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic and Environmental Risk Factors of Tuberculosis in Wonosobo, Central Java, Indonesia

Abstract: This study discusses the dominant socio-economic and environmental risk factors for TB disease. The design of this study was a case-control study with 70 case samples and control with a contribution of n = 1. Variables from this study contacted personal, ventilation of the house, humidity, the temperature of the house, density of the house, kitchen, and family earnings. Multivariate data analysis uses multiple logistic regressions. The study notes that from 140 samples, 47% have basic education, and 30% are fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
5
1
2
Order By: Relevance
“…The questionnaire was suitably developed to address the complexities of the diverse regions in Indonesia and the unique healthcare challenges encountered. Indonesia has been reported to show significant regional disparities in healthcare infrastructure, patient attitudes, and socioeconomic influences ( Erawati and Andriany, 2022 ; Siswantining et al, 2020 ; Pratiwi et al, 2020 ). Considering these disparities, the questionnaire was designed to be adaptable and relevant across different areas of the country, but some regional customization was required before the broad implementation ( Mahmudiono and Laksono, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was suitably developed to address the complexities of the diverse regions in Indonesia and the unique healthcare challenges encountered. Indonesia has been reported to show significant regional disparities in healthcare infrastructure, patient attitudes, and socioeconomic influences ( Erawati and Andriany, 2022 ; Siswantining et al, 2020 ; Pratiwi et al, 2020 ). Considering these disparities, the questionnaire was designed to be adaptable and relevant across different areas of the country, but some regional customization was required before the broad implementation ( Mahmudiono and Laksono, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic life afects lifestyle by changing the priorities such as care seeking, nutritional status, and living conditions. Low socioeconomic status and poverty are important indicators of TB documented in many studies in diferent settings with increasing poverty increasing the risk of TB [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…The study results in Wonosobo, Central Java, showed the same results as this study: there was a significant relationship between housing density and TB incidence. Pratiwi, Pramono and Junaedi mentioned that someone who lives in an area with a high density of housings has 5 times higher risk of being exposed to TB than those who live in a low density (16). This shows that the density of housings affects TB incidence because dense environments may also have poor sanitation, slum areas, lots of garbage, and poorly maintained grounds, especially in developing countries (6).…”
Section: Discussionmentioning
confidence: 99%